THE STRATEGY TO IMPROVE SALESPERSON’S PERFORMANCE BY SALESPERSON’S TECHNICAL COMPETENCY, SALES SOFT CAPABILITY, SERVICE ORIENTATION, AND ADAPTIVE SELLING - Zakaria, Shandy Ibnu; Ferdinand, Augusty Tae; Raharjo, Susilo Toto (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2017)
This research aims to find out whether a salesperson’s technical competention, sales soft capability, service orientation, and adaptive selling have any impact to improve salespersons’ performance in a case study of Prepaid Television Channel Transvision’s Salesperson in distribution area Central Java and Special Region of Yogyakarta. This research takes 102 respondents as the object and uses sampling technique.Data analysis technic that is used in this research is structural equation model (SEM) from AMOS 22 software. The test result done using SEM shows the goodness of fit full model criteria which are Chi-square = 67,203; Probability = 0,035; CMIN/DF = 1,400; GFI = 0,905; AGFI = 0,845, TLI = 0,904; CFI = 0,930; dan RMSEA = 0,063. Therefore, it can be said that the model in this research is qualified to use.  The research findings show that from 6 hypothesis being tested, there are 2 hypothesis rejected and 4 hypothesis accepted. The first hypothesis which is salesperson’s technical competency has positive impact and is significant. The second hypothesis which is salesperson’s technique has positive impact and is significant. The third hypothesis sales soft capability has positive impact but is not significan. The fourth hypothesis sales soft capability has positive impact and is significant. The fifth hypothesis service orientation has positive impact and is significant. The sixth hypothesis which is adaptive selling has positive impact but is not significant with value. This research has several limitation and gives the agenda for the further researches to be done after this research.